Sebuah Analisis Pengalaman Batin Penderita Bipolar Disorder Pada Pemeran Utama Pada Film Berjudul Touched With Fire Oleh Paul Dalio - Wulandari, Cahya Suci; Widyahening, Ch. Evy Tri (English Education Department Slamet Riyadi University Surakarta, 2024)
The objectives of this research were: 1) To find out the inner experiences that had been experienced by Marco and Carla as bipolar disorder sufferer in a film entitled Touched With Fire By Paul Dalio “TWF”; 2) To find out the impacts of inner experience that had been experienced by Marco and Carla as bipolar disorder sufferer to theirself in a film entitled TWF By Paul Dalio; 3) To find out the impacts of inner experience that had been experienced by Marco and Carla as bipolar disorder sufferer to the other character in a film entitled TWF By Paul Dalio. The researcher used qualitative research method with type of library research. This research used primary and secondary data as the sources. The technique of data collection was listen, watch, read, and note down important points of the film. In the technique of analyzing data, the researcher used qualitative data analysis by Miles, Huberman, and Saldana, such as data collection, data display, conclusion drawing and verification. To find the validity of the research, was used by triangulation data. The result of the research showed that: 1) Marco and Carla experienced some inner experience relating to their bipolar disorder. They are thoughts; imagination; feelings and emotions; moral or ethical feelings. 2) The inner experience that had been experienced by them has some impact both to theirself and the other. Keywords :Touched With Fire, Paul Dalio, Bipolar, Inner Experience.